Efficient and reversible CO2 capture by amine functionalized-silica gel confined task-specific ionic liquid system - Javad Aboudi; Majid Vafaeezadeh (Journal of Advanced Research, 2015)
Simple, efficient and practical CO2 capture method is reported using task-specific ionic liquid (IL) supported onto the amine-functionalized silica gel. The results have been shown that both the capacity and rate of the CO2 absorption notably increase in the supported IL/molecular sieve 4 Å system in comparison of homogeneous IL. Additionally, it has shown that the prepared material is capable for reversible carbon dioxide absorption for at least 10 cycles without significant loss of efficiency. The presence of the amine-based IL and the surface bonded amine groups increase the capacity of CO2 absorption even in a CO2/CH4 gas mixture through the formation of ammonium carbamate onto the surface of mesoporous material.